PENERAPAN STRATEGI PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII. 6 SMPN 12 PEKANBARU - Murniati, eva (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2019)
The selection of the right learning method greatly affects the high and low learning outcomes of students. At Pekanbaru SMPN 12, the learning strategies used by science teachers are still conventional. Learning has been teacher-centered and communication runs in one direction. The lecture method does not provide space for students to develop their knowledge. Passive learners and learning become boring. So the science learning outcomes of class VII.6 students are low. Index Card Match strategy is an active learning method for reviewing subject matter with a technique of finding index card pairs which are answers or questions while learning about a concept or topic in a pleasant atmosphere. One of them is by using Index Card Match learning strategies. This study aims to obtain data on the extent to which the application of Index Card Match can improve science learning outcomes of students of class VII.6 Pekanbaru 12 SMP. This research uses Classroom Action Research with a recycling cycle which consists of four stages, namely (a) planning, (b) implementation, (c) observation and (d) reflection. Data is collected through observation sheets, documentation studies, and tests in each cycle. The results showed that, on average, student learning outcomes increased. Percentage of completeness also increases. In the pre-study the percentage of completeness was 37.5%. the first cycle was 66.66% and the second cycle was 88.6%